Proceeds of Criminal Offense according to Article 240 of the Criminal Code - Dušan Jovanovič; Miha Bratina (Naše gospodarstvo/Our economy, 2013)
In the article, the authors analyze the elements of a criminal offense according to Ar- ticle 240 of the Criminal Code (KZ-1) from the corporate point of view. They focus on the proceeds of the criminal offense according to the aforementioned article, which are its core element. The article also states and substantiates the exposed legal questions connected to the extensive case law of foreign courts. Some practi- cal examples are provided of legal proceedings within corporate law, where lately some tendencies for supervisory and management board members to commit crimi- nal offenses have appeared.